2021
DOI: 10.2110/carnets.2021.2110
|View full text |Cite
|
Sign up to set email alerts
|

Another thermophilic "Miocene survivor" from the Italian Pliocene: A geologically young occurrence of the pelagic eagle ray Aetobatus in the Euro-Mediterranean region

Abstract: Aetobatus (Myliobatiformes: Aetobatidae) is a living genus of eagle rays that occurs in shallow-marine, tropical and subtropical environments of the Atlantic, Pacific, and Indian Oceans. Nowadays, Aetobatus does not inhabit the cool- to warm-temperate European and Mediterranean waters, though it is known from this broad region by virtue of several fossil teeth ranging chronostratigraphically from the lower Palaeogene to the upper Neogene. The present paper reports on a fossil aetobatid tooth discovered in mid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…As such, it supports the notion that the occurrence of the holotype of C. thermophila in present-day Italy does not testify an Atlantic vagrant individual whose remains serendipitously fossilised in the Mediterranean Sea. Recent palaeoclimatic reconstructions for the Early Pliocene Mediterranean Sea suggest surface seawater temperatures about 2-3°C higher than today (e.g., Prista et al 2015;Ragaini et al 2019;Coletti et al 2021), as also supported by a conspicuous fossil record of thermophilic marine vertebrates (e.g., Mora Morote 1996, 1997Collareta et al 2017Collareta et al , 2021a. Besides several specimens of the purportedly thermophilic sirenian Metaxytherium subapenninum (Sorbi et al 2012), the deposits in which MSNUP I-16153 was found feature a high concentration of fossil teeth belonging to tropical or subtropical elasmobranch species, such as the bull shark Carcharhinus leucas and the tiger shark Galeocerdo cuvier (Simpfendorfer & Burgess 2009;Ferreira & Simpfendorfer 2019).…”
Section: Discussionmentioning
confidence: 98%
“…As such, it supports the notion that the occurrence of the holotype of C. thermophila in present-day Italy does not testify an Atlantic vagrant individual whose remains serendipitously fossilised in the Mediterranean Sea. Recent palaeoclimatic reconstructions for the Early Pliocene Mediterranean Sea suggest surface seawater temperatures about 2-3°C higher than today (e.g., Prista et al 2015;Ragaini et al 2019;Coletti et al 2021), as also supported by a conspicuous fossil record of thermophilic marine vertebrates (e.g., Mora Morote 1996, 1997Collareta et al 2017Collareta et al , 2021a. Besides several specimens of the purportedly thermophilic sirenian Metaxytherium subapenninum (Sorbi et al 2012), the deposits in which MSNUP I-16153 was found feature a high concentration of fossil teeth belonging to tropical or subtropical elasmobranch species, such as the bull shark Carcharhinus leucas and the tiger shark Galeocerdo cuvier (Simpfendorfer & Burgess 2009;Ferreira & Simpfendorfer 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, along the Pliocene coasts of Tuscany, a largely modern carcharhine assemblage coexisted along with "Miocene survivors" among both the sharks (e.g., the extinct 1941;COLLARETA et al 2017COLLARETA et al , 2021b) -an observation that evokes a rather gradual transition from the pre-evaporitic Mediterranean assemblages of the Tortonian and Messinian (e.g., MENESINI 1967MENESINI , 1969ARAMBOURG 1927;WARD & BONAVIA 2001) through the Messinian Salinity Crisis (cf. discussion in CARNEVALE et al 2019) and the subsequent Pliocene.…”
Section: General Discussion and Palaeobiogeographic Inferencesmentioning
confidence: 99%
“…Abundant remains of both marine and nonmarine vertebrates have been collected from several localities of the Valdelsa Basin [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. In particular, the specimens discussed herein have been collected by one of us (SC) at two different Pliocene outcrops.…”
Section: Stratigraphic Frameworkmentioning
confidence: 99%